The use of a modified tanagho flap in the repair of posterior urethral stricture after primary exstrophy closure. Issue 1 (February 2023) - Guan, Hannah; Sholklapper, Tamir; Crigger, Chad; Haney, Nora; Harris, Thomas G.W.; Gearhart, John P.
Summary: Introduction: In patients with classic bladder exstrophy (CBE), posterior urethral strictures after primary bladder closure can be difficult to manage and therefore necessitate alternative techniques in reconstruction of the proximal urethra. There is a paucity of literature describing treatment and management of posterior urethral stricture arising after repair of classic bladder exstrophy. Objective: To describe the technique of a bladder neck reconstruction (BNR) with a modified Tanagho anterior detrusor flap in the treatment of posterior urethral stricture arising after repair of classic bladder exstrophy. Patients and methods: A prospectively maintained, IRB-approved database of 1401 exstrophy-epispadias patients was reviewed for patients who underwent bladder neck or proximal urethral reconstruction with modified Tanagho flap for proximal urethral stricture disease from the time period of 1975–2021. A total of 5 patients (1 female and 4 males) with classic bladder exstrophy who underwent proximal urethral reconstruction with modified Tanagho flap were identified. Of these 5 patients, the 1 female patient was treated for ongoing incontinence, not posterior urethral stricture, and was thus excluded from this report. Outcomes measured included post operative bladder capacity, post-operative continence status, upper urinary tract status, and stricture recurrence. Results: Four male patients with CBE were treated for posterior urethral strictures and are reviewed here. Three patients underwent successful primary closure (1 via modern staged repair of exstrophy (MSRE) and 2 via complete primary repair of exstrophy (CPRE)), and 1 patient (MSRE) required repeat closure at the time of stricture repair. Mean age at BNR Tanagho flap was 3.8 (range 2.3–5.0) years. All patients remained stricture free with post-operative urinary incontinence; 2 patients underwent subsequent elective bladder neck transection to achieve continence. Mean follow up 9.9 (range 2.1–15.6) years. Discussion: All 4 patients had excellent long term success rates, comparable to results reported in several adult studies utilizing a modified Tanagho flap in women with post-traumatic bladder neck contractures. In addition, our technique described here shares similarities with both the originally described Tanagho flap as well as with a dorsal onlay graft urethroplasty. Conclusion: In this limited series, modified Tanagho flap reconstruction is effective in treating posterior urethral stricture disease in CBE. This technique adds a valuable adjunct to the armamentarium of surgical options for this difficult to manage condition. Summary Figure A-E: Cystotomy with creation of modified Tanagho Flap.